(untitled) (Ágora Journal, 2023)
This article aims to discuss the migratory process in Espírito Santo in four periods: from 1813 to 1900, when the first immigrants encouraged by colonial policy reached the end of the cycle of international immigration; from 1910 to 1950, related to the expansion of colonizing agricultural fronts in the interior of the state with the expansion of intra and interstate national mobility; from 1960 to 1990, articulating the coffee eradication policy and national and foreign productive investments, from 2000 onwards with the growth of the oil industry, driven by economic and population growth, including the 20-25 state plan. Finally, we show that the migration process accompanied and helped to forge the current sociodemographic and economic structure of Espírito Santo, which is essential to characterize and understand the current context of the state.